Optimization of Traffic Signals at Road Intersections - Supriya B.Shinde, Krantikumar V. Mhetre, Shital A. Patage, Sachin J.Yadav (Mathematical Statistician and Engineering Applications, 2022)
Traffic congestion has been one of the major issues that most cities are facing now, even though Proper measures are being taken in order to mitigate and reduce its impact. In the recent years, traffic congestion is becoming one of the main challenge for engineers, which is a problem for pedestrians and other road users. There are many reasons behind this scenario. One of the main reasons is the existence of structures along the main roads of the city and other illegal possession of shops on footpaths, which attract a huge amount of visitors and they form a long queue in search of parking their vehicle. Rapid growth in vehicle ownership is the other reason for congestion which cannot be completely escaped. Decreased air quality and increased travel time are the impacts of congestion.